Pengaruh Corporate Governance terhadap Kinerja Perusahaan Transportasi yang Terdaftar di Bursa Efek Indonesia (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to analyze the effect of Corporate Governance on the financial performance of transportation companies listed on the Indonesia Stock Exchange (IDX). Financial performance is measured using Return on Assets (ROA) as an indicator of the company’s ability to efficiently manage its assets to generate profits. Corporate Governance is proxied by the presence of independent commissioners and institutional ownership. This research adopts a quantitative approach using secondary data obtained from the annual reports of transportation companies for the period 2023–2025. Data analysis is conducted using multiple linear regression with the assistance of SPSS software to examine both partial and simultaneous relationships among variables. The results indicate that independent commissioners have a positive and significant effect on ROA, suggesting that effective oversight and independence of the board can enhance asset management efficiency and overall financial performance. In contrast, institutional ownership does not have a significant effect on ROA, indicating that institutional shareholding does not necessarily guarantee effective managerial monitoring. Simultaneously, Corporate Governance has an effect on financial performance, although its contribution remains moderate. This study highlights the importance of effective implementation of Corporate Governance principles in improving the financial performance of transportation companies.